Control Chart Application to Monitoring MFI’s Mission Change for Women Borrowers under Adverse Economy - Sohn, So Young; Ji, Eun Jeong; Han, Eun Jin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
One of the main missions of Microfinance Institutions (MFIs) is to improve the status of under-privileged people. However, MFI’s mission drift or enhancement can occur under adverse economic condition. In this paper, we investigate the direction of changes in supporting women borrowers who make up the majority of the poor by using the lending patterns of Latin American and Caribbean MFIs during the recent global financial crisis. P control chart is applied to detect assignable changes in the lending rate to woman over different MFIs. In order to identify related characteristics to the outlying MFIs identified from the P control chart, we perform logistic regression analysis. Our study results can contribute to understand MFI’s mission change in terms of supporting women borrowers and identify the related characteristics of MFIs.